2015
DOI: 10.1016/j.bbr.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Roles of human hippocampal subfields in retrieval of spatial and temporal context

Abstract: While numerous studies indicate the involvement of the hippocampus in encoding and retrieval of spatial and temporal context, the neural basis of spatial and temporal processing within the hippocampal circuit remains unclear. We employed a novel paradigm in which participants encoded stores within a spatial layout by visiting them in a specific temporal order. Participants then underwent high-resolution functional magnetic resonance imaging (fMRI) targeting the hippocampus while retrieving details of the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
30
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 64 publications
12
30
2
Order By: Relevance
“…During testing of memories for the distances and timing between key events, subject-specific neural similarity in the hippocampus scaled with the remembered proximity of events both in space and time. Notably, unlike in the Kyle et al (2015) report, in this study subjects’ judgments about space and time were correlated and the integrated spatial and temporal patterns did predict space and time judgments. However, there were also individual influences of spatial and temporal coding when the other variable was removed in the analysis, confirming a degree of independence between the neural ensemble patterns that represent space and time.…”
Section: Are Time and Space Separated Or Integrated Within The Hippoccontrasting
confidence: 98%
See 1 more Smart Citation
“…During testing of memories for the distances and timing between key events, subject-specific neural similarity in the hippocampus scaled with the remembered proximity of events both in space and time. Notably, unlike in the Kyle et al (2015) report, in this study subjects’ judgments about space and time were correlated and the integrated spatial and temporal patterns did predict space and time judgments. However, there were also individual influences of spatial and temporal coding when the other variable was removed in the analysis, confirming a degree of independence between the neural ensemble patterns that represent space and time.…”
Section: Are Time and Space Separated Or Integrated Within The Hippoccontrasting
confidence: 98%
“…To explore potential differences among hippocampal subdivisions and whether space and time are represented by the same or different neural ensemble activity patterns, Kyle et al (2015) employed high-resolution fMRI on human subjects during memory retrieval after playing a virtual reality game where they visited stores in a particular order within a specific spatial layout. During retrieval participants made independent judgments either about near or far intervals within the spatial layout or about temporal sequence.…”
Section: Are Time and Space Separated Or Integrated Within The Hippocmentioning
confidence: 99%
“…This unified account of spatial context, temporal context and spatiotemporal context aligns well with recent fMRI studies virtual reality suggesting not only that similar regions participate in recovery of spatial and temporal context [66, 67, 64] (see also Fig. 2B).…”
Section: Advances In the Theory Of Temporal And Spatial Contextsupporting
confidence: 88%
“…Successful memory was associated with maintenance during the delay of the same hippocampal activation pattern observed during encoding. Supporting theories about the importance of context coding, RSA studies have shown that successful memory is associated with reinstatement of the representation of the relevant spatial or temporal context occupied by the item during initial study (Flegal et al 2014, Kyle et al 2015; for reviews, see Davachi 2006, Eichenbaum et al 2007) and with increased dissimilarity of spatial and temporal context representations between memories (Copara et al 2014). …”
Section: How Are Memories Organized By Neural Network Within the Hipmentioning
confidence: 92%